"You'll hear me and you'll understand me": the political and intellectual journey of Diva Moreira (PerCursos, 2024)
In this article we will delve into the jouney of sociologist and black activist Diva Moreira, specifically on the way she articulates discussions of race, gender and class in her own political action. The article is a part of the field of Intellectual History and Feminism, understanding Diva Moreira as a black intellectual who was responsible for the diffusion of ideas and debates about anti-racist struggles. As primary sources, interviews were granted by Museu da Pessoa (2005), CPDOC-FGV (2007), and Fundação João Pinheiro (2021). As secondary sources, the reports of the National Information Service (SIAN). This activist's history sets an example for the political and cultural production from the margin of black women, broadening our understanding of these women and their political action.
Keywords: Black Women; black movement; intellectual history